Absolute configurations of talaromycones A and B, α-diversonolic ester, and aspergillusone B from endophytic Talaromyces sp. ECN211 - Nakashima, Ken-ichi; Tomida, Junko; Hirai, Takao; Kawamura, Yoshiaki; Inoue, Makoto (Beilstein Journal of Organic Chemistry, 2020)
Talaromycones A (1) and B (2), new xanthenediones, were isolated from the cultures of Talaromyces sp. ECN211, an endophytic fungus, along with α-diversonolic ester (3), aspergillusone B (4), glauconic acid (5), and rosellisin (6). The planar structures of 1 and 2 were elucidated by extensive spectroscopic analyses. Furthermore, the absolute configurations of 1–4 were determined by single-crystal X-ray diffraction and electronic circular dichroism spectroscopy (ECD). In addition, the crystallographic data for 5 were updated for the first time in over 50 years.
Keywords: absolute configuration; endophytic fungus; glauconic acid; Talaromyces; tetrahydroxanthone; xanthenedione

(untitled) - Masters, K.-S.; Bräse, S. (Chem. Rev., 2012)

(untitled) - Zhang, W.; Krohn, K.; Zia-Ullah; Flörke, U.; Pescitelli, G.; Di Bari, L.; Antus, S.; Kurtán, T.; Rheinheimer, J.; Draeger, S.; Schulz, B. (Chem. – Eur. J., 2008)

(untitled) - Holker, J. S. E.; Mulheirn, L. J. (Chem. Commun., 1968)

(untitled) - Wijeratne, E. M. K.; Turbyville, T. J.; Fritz, A.; Whitesell, L.; Gunatilaka, A. A. L. (Bioorg. Med. Chem., 2006)

(untitled) - Nicolaou, K. C.; Li, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Trisuwan, K.; Rukachaisirikul, V.; Kaewpet, M.; Phongpaichit, S.; Hutadilok-Towatana, N.; Preedanon, S.; Sakayaroj, J. (J. Nat. Prod., 2011)

(untitled) - Nakashima, K.-i.; Tomida, J.; Hirai, T.; Kawamura, Y.; Inoue, M. (J. Nat. Prod., 2019)

(untitled) - Nakashima, K.-i.; Tomida, J.; Kamiya, T.; Hirai, T.; Morita, Y.; Hara, H.; Kawamura, Y.; Adachi, T.; Inoue, M. (Tetrahedron Lett., 2018)

(untitled) - Nakashima, K.-i.; Tomida, J.; Hirai, T.; Kawamura, Y.; Inoue, M. (J. Nat. Med., 2019)

(untitled) - Raja, H. A.; Miller, A. N.; Pearce, C. J.; Oberlies, N. H. (J. Nat. Prod., 2017)

(untitled) - Barton, D. H. R.; Sutherland, J. K. (J. Chem. Soc., 1965)

(untitled) - Barton, D. H. R.; Jackman, L. M.; Rodriguez-Hahn, L.; Sutherland, J. K. (J. Chem. Soc., 1965)

(untitled) - Barton, D. H. R.; Godinho, L. D. S.; Sutherland, J. K. (J. Chem. Soc., 1965)

(untitled) - Nieminen, S.; Tamm, C. (Helv. Chim. Acta, 1981)

(untitled) - Nair, M. S. R. (Phytochemistry, 1976)

(untitled) - Ferguson, G.; Sim, G. A.; Robertson, J. M. (Proc. Chem. Soc., 1962)